A realistic approach to treatment design based on impulsive synchronization. (January 2022) - Garjani, Hasti; Ozgoli, Sadjaad
Abstract: Motivated by the need for a systematic methodology for treatment design, especially considering the fact that drugs are consumed in specific dosages at a time(not continuously), the aim of this work is to design an impulsive treatment plan which is applicable in real world. In this study, an innovative methodology for designing an impulsive treatment program is proposed which synchronizes the dynamics of the patient as the slave subsystem with those of the healthy person as the master subsystem. It is generally accepted that controllers based on impulsive synchronization have great performance on chaotic systems; however, this article suggests an innovative approach for synchronizing two non-chaotic systems with different dynamics. It is mathematically proved that the proposed method successfully synchronizes the two systems. An algorithm is then provided to design treatment based on synchronization. To validate the viability of the proposed method, design parameters are adjusted for diseases, and diabetes and cancer treatment are considered as case studies. The performance of the treating plan is demonstrated via simulations.